Il significato metafisico della teoria della conoscenza fenomenologica - Trizio, Emiliano (Bollettino Filosofico, 2018)
Recently, a number of publications (e.g. Tengelyi 2014, Zahavi 2017) have renewed the interest for the relation between phenomenology and metaphysics. This issue appears crucial both for understanding Husserl’s thought per se, and for a systematic appraisal of its relations with postHusserlian phenomenology as well as with contemporary analytic debates about metaphysics. In this paper, I will argue that, contrary to what Zahavi and other have claimed, metaphysical interests played an essential role even before the Logical Investigations and that, by acknowledging it, we can better appreciate the metaphysical implications of Husserl’s later transcendental idealism. This conclusion will rest on 1) a careful investigation of Husserl’s own different notions of metaphysics and 2) an analysis of his views about the relations between metaphysics and the theory of knowledge.